Arnebia euchroma, a Plant Species of Cold Desert in the Himalayas, Harbors Beneficial Cultivable Endophytes in Roots and Leaves - Jain, Rahul; Bhardwaj, Priyanka; Pandey, Shiv Shanker; Kumar, Sanjay (Frontiers in Microbiology, 2021)
The endophytic mutualism of plants with microorganisms often leads to several benefits to its host including plant health and survival under extreme environments. Arnebia euchroma is an endangered medicinal plant that grows naturally in extreme cold and arid environments in the Himalayas. The present study was conducted to decipher the cultivable endophytic diversity associated with the leaf and root tissues of A. euchroma. A total of 60 bacteria and 33 fungi including 9 yeasts were isolated and characterized at molecular level. Among these, Proteobacteria was the most abundant bacterial phylum with the abundance of Gammaproteobacteria (76.67%) and genus Pseudomonas. Ascomycota was the most abundant phylum (72.73%) dominated by class Eurotiales (42.42%) and genus Penicillium among isolated fungal endophytes. Leaf tissues showed a higher richness (Schao1) of both bacterial and fungal communities as compared to root tissues. The abilities of endophytes to display plant growth promotion (PGP) through phosphorus (P) and potassium (K) solubilization, production of ACC deaminase (ACCD), indole acetic acid (IAA), and siderophores were also investigated under in-vitro conditions. Of all the endophytes, 21.51% produced ACCD, 89.25% solubilized P, 43.01% solubilized K, 68.82% produced IAA, and 76.34% produced siderophore. Six bacteria and one fungal endophyte displayed all the five PGP traits. The study demonstrated that A. euchroma is a promising source of beneficial endophytes with multiple growth-promoting traits. These endophytes can be used for improving stress tolerance in plants under nutrient deficient and cold/arid conditions.